Economic analysis of afforestation projects for carbon sequestration: a case study in Patagonia, Argentina - Salvador, Gustavo Marcelo (Faculty of Agricultural Sciences, Georg-August-University of Göttingen (Alemania), 2020)
Tesis presentada para optar al título de Magister Scientiae en Agronegocios Internacionales, de la University of Göttingen (Alemania), en 2004